Views on the incorporation of Geolocation Devices in Field Trips - Marta Magallón; Cristina Mercader (Universidad Nacional, Costa Rica, 2022)
Introduction. Some outdoor activities may have been self-constrained due to the fear of students getting lost. It is a limitation for the school staff and a constraint for students. However, few studies have been developed regarding the possibilities of geolocation as a solution. Aim. The study aims to explore this brand-new issue that could benefit the management of field trips. The study was developed from a mixed-method perspective with a sample of 51 members of an educational community. Methodology. The methodology included surveys to analyze the level of students' autonomy and the views on security by parents, teachers, directive team, and students with the possibility of incorporating these devices. Results. Show that using geolocation devices in field trips improves the sense of security and allows students to develop autonomous skills. Conclusion. Geolocation in field trips has great potential, but it is an understudied field that needs more research and discussion to ensure data privacy.